Soil, Water and Nitrates Management in Horticultural Production - Machado, Rui Manuel Almeida (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Soil, water, and nitrogen management are critical for crop productivity and quality in horticulture as well as for reducing negative impacts on ecosystems and greenhouse gas emissions. This Special Issue is a collection of seven important research works addressing solutions or strategies that can be implemented in order to use these three factors of production in a more sustainable way and to reduce inorganic nitrogen applications by considering the great importance of circular agriculture and the use of microorganisms. Aside from the relevance of the topics in this Special Issue, the studies included within it may trigger the development of new strategies for more sustainable and environmentally friendly intensive agriculture.